2007
DOI: 10.1111/j.1473-2165.2007.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative benefit of two thermal spring waters after photodynamic therapy procedure

Abstract: This comparative clinical trial demonstrates that ATSW, a low mineral content spring water, can be useful after ALA-PDT in reducing postprocedure cutaneous inflammation and patient discomfort better than a high mineral content spring water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…In the present study, we observed a significant reduction in pain, cutaneous dryness, and redness/erythema in the TSW‐treated side of the face following fractional laser irradiation. These results are in line with previous studies showing the soothing and anti‐irritant properties of TSW in various skin conditions such as irritation secondary to topical retinoïc acid, and after specific procedures like ALA‐PDT 7,12,13 . TSW has also been shown to decrease local skin temperature, as measured by thermography after vascular laser treatment in patients suffering from rosacea 14 .…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we observed a significant reduction in pain, cutaneous dryness, and redness/erythema in the TSW‐treated side of the face following fractional laser irradiation. These results are in line with previous studies showing the soothing and anti‐irritant properties of TSW in various skin conditions such as irritation secondary to topical retinoïc acid, and after specific procedures like ALA‐PDT 7,12,13 . TSW has also been shown to decrease local skin temperature, as measured by thermography after vascular laser treatment in patients suffering from rosacea 14 .…”
Section: Discussionsupporting
confidence: 91%
“…Thermal mineral water treatments have been demonstrated to promote healing of skin irritations (5) and to improve skin restoration after cosmetic aggressive procedures (6,7). Such effects are likely to be related to some anti-inflammatory action (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Pagliaro et al (Table III) investigated cold air anesthesia in ALA-PDT for BCC, finding a lower mean duration of pain compared to the ambient air group 72 . In twenty-one additional studies, some form of local cooling was also offered to the patients 5111525273038434663666870717374 . Possible mechanisms for pain reduction include a reduction of tissue metabolism (thus reducing the effects of injury), and vasoconstriction, which would reduce the inflow of inflammatory mediators and thereby decrease edema.…”
Section: Pain Managementmentioning
confidence: 99%